2020
DOI: 10.1021/acs.orglett.0c01165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Taxol Core via Catalytic Asymmetric 1,4-Addition of an Alkylzirconium Nucleophile

Abstract: The Taxol core was prepared in five steps via a key copper-catalyzed asymmetric conjugate addition (ACA) trapping sequence. The use of a bromodiene derived alkylzirconium nucleophile followed by trapping with POCl3/DMF give a highly functionalized intermediate featuring a quaternary centre in 69% yield and 92% ee. After 1,2-addition, Suzuki-Miyaura cross coupling, allylic oxidation, and a type II intramolecular Diels-Alder reaction the taxol core was obtained in 11% overall yield with 92% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Earlier works in this field focused on using these enolates in aldol, Mannich, Michael additions, or nucleophilic substitutions [21] . Recent effort of the research community focuses on utilizing either less explored enolates, [22] substrates, [23] or trapping reactions [24] . Our lab's interest in expanding this methodology aims on using carbocations or their equivalents in Cu‐catalyzed ACAs of organometallic reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier works in this field focused on using these enolates in aldol, Mannich, Michael additions, or nucleophilic substitutions [21] . Recent effort of the research community focuses on utilizing either less explored enolates, [22] substrates, [23] or trapping reactions [24] . Our lab's interest in expanding this methodology aims on using carbocations or their equivalents in Cu‐catalyzed ACAs of organometallic reagents.…”
Section: Methodsmentioning
confidence: 99%
“…[21] Recent effort of the research community focuses on utilizing either less explored enolates, [22] substrates, [23] or trapping reactions. [24] Our lab's interest in expanding this methodology aims on using carbocations or their equivalents in Cu-catalyzed ACAs of organometallic reagents. We have shown that stabilized carbocations such as tropylium or sulfur-stabilized cations are compatible with Grignard or organozirconium reagents.…”
mentioning
confidence: 99%
“…In 2020, Fletcher and co-workers 152 reported a concise and enantioselective approach to Taxol core (Scheme 29D). Type II IMDA cycloaddition of intermediate 211 with TiCl 4 afforded the tricyclic compound 212 in 35% yield, albeit as a 1:1 mixture of diastereomers at C1.…”
Section: Model Studiesmentioning
confidence: 99%
“…66 This reaction was recently employed in the total synthesis of taxol core derivative 47 (Scheme 13). 67 This work improved on Baran's elegant synthesis of taxadienone, 68 which utilized the ACA of Me 3 Al using Alexakis's protocol. 69 The advantage of the use of organozirconium reagents was in the streamlined installation of the alkenyl side chain at the C3-position.…”
Section: Scheme 12 the First Zr-enolate Trapping Reactions Initiated mentioning
confidence: 99%